Macromedia Dreamweaver 8 visual encyclopedia - Cavanaugh, Kim (Wiley, 2006)
f you prefer to see what things look like and how to perform a task, instead of just being told, this is your ideal A to Z reference. Part I shows every Dreamweaver 8 tool and how to use it. Part II provides step-by-step instructions for more than 140 key tasks and techniques. Both are arranged alphabetically and illustrated in full color. It's the ultimate Visual resource--you'll see!